Comparative Study of Thymidine Kinase -1 and Total Antioxidant Capacity in Iraqi Children with Platelet Count Disorder - Jabar, Manar Satar; Abass, Eiman AA. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This study aimed to find relationship between thymidine kinase-1 (TK-1) as tumor marker and total antioxidant capacity (TAC) in Iraqi children patients with thrombocytopenia and with thrombocytosis. The present study conducted 60 children patients (30 patients with idiopathic thrombocytopenia purpura (ITP) and 30 patients with thrombocytosis caused by leukemia) attending the Children Fever Hospital in the Medical City / Baghdad, and 30 healthy children as a control group. All study groups were with range ages (1-15) years, and they were diagnosed by assay of platelet count, Prothrombin Time   (PT), and partial Thromboplastin Time (PTT). The results shown elevation  in plasma TK-1 and TAC values in children patients with thrombocytopenia and with thrombocytosis when compared with control group, and there was no significant different in TK-1 level and a significant different in TAC level in two patients groups. There were a highly significant positive correlation between TK-1 and TAC levels in both Iraqi children patients with thrombocytopenia and with thrombocytosis. The current study concluded that TK-1 may be a novel biomarker for platelet count disorder disease and there was a probability of expose these patients for tumor diseases.